UPAYA PEMBENTUKAN AKHLAK MELALUI PROSES BELAJAR MENGAJAR DI SMK NASIONAL MALANG - Alfian Wahyudi; Khoirul Asfiyak; Ika Ratih Sulistiani (VICRATINA, 2019)
This study attempts to described the result of research by researcher, pertaining to the effort to the formation of morals. The research uses a qualitative approach was adopted. The qualitative study here examines the state or ongoing problems, is expected to obtain information proper and a full picture on a study.  The subject matter of the back out research were students majoring in the of the motorcycle. The technique of the collection of data deal is observation and the objective of the interview. The formation of attitude is the duty teachers and parents. A good attitude can be formed with a fine. But as soon as we a manifestation of it’s a the implantation of the in forming remembrance of the home in a student to lose their via a variety of kinds of other activities. There are some steps that must be implemented by the teachers especially PAI teacher in the school. Where in this student can implementing activities inside or outside learning process. The first is planning. Planning done as moral preliminary preparation in forming students. The second is the implantation. The implementation of the done in the same manner as a manifestation of it’s the implementations of the planning that is has already been prepared. The third evaluation. The evaluation is done to be able to measure their success in implementing students attitude. So thet they can be more easily in knowing would have maximum and effect the already performed in shapping student attitude.